El juego como estrategia de aprendizaje en el proceso educativo de los niños y niñas del primer año de educación básica de las escuelas fiscales mixtas: Jaime Roldós Aguilera y Combate de Pilo de la ciudad de Machala, en el período 2012-2013. - Navarrete Jaramillo, Marisol del Rocío (2013)
This research is based on the study of the incidence of the game as learning strategies in the educational process of the children in the first year of basic education in mixed public schools: President Jaime Roldós Aguilera and fighter pilo of city of Machala, where facilitate the incorporation of an innovative plan for a solution of problems with regard to the educational process.